2013
DOI: 10.5194/bg-10-7361-2013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of belowground litter addition, increased precipitation and clipping on soil carbon and nitrogen mineralization in a temperate steppe

Abstract: Abstract. Soil carbon (C) and nitrogen (N) cycling are sensitive to changes in environmental factors and play critical roles in the responses of terrestrial ecosystems to natural and anthropogenic perturbations. This study was conducted to quantify the effects of belowground particulate litter (BPL) addition, increased precipitation and their interactions on soil C and N mineralization in two adjacent sites where belowground photosynthate allocation was manipulated through vegetation clipping in a temperate st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 64 publications
0
27
2
Order By: Relevance
“…Such lack of response of the root biomass to precipitation variability was likely because nutrients limit root growth along the gradient. Although we cannot prove this point, manipulating N and water experiments demonstrated that N addition accelerated plant growth, especially root growth, whereas there was no effect of water addition on root biomass in this study region (Lü et al, 2010;Ma et al, 2012Ma et al, , 2013Xiao et al, 2007).…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…Such lack of response of the root biomass to precipitation variability was likely because nutrients limit root growth along the gradient. Although we cannot prove this point, manipulating N and water experiments demonstrated that N addition accelerated plant growth, especially root growth, whereas there was no effect of water addition on root biomass in this study region (Lü et al, 2010;Ma et al, 2012Ma et al, , 2013Xiao et al, 2007).…”
Section: Discussioncontrasting
confidence: 61%
“…Higher mineralization processes typically indicate instability of soil organic matter (Trumbore, 1997). There is plenty of evidence to demonstrate that soil respiration and net N mineralization increased with precipitation and water availability in water-limited regions (Sierra, 1997;Barrett et al, 2002;Paul et al, 2003;McCulley et al, 2005;Ma et al, 2013). According to Stanford and Epstein (1974), the maximum net N mineralization rate occurs when soil moisture is close to field capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were found in other ecosystems (Huang et al 2004;Mungai and Motavalli 2006;Jiang et al 2013;Begum et al 2014). The enhanced emissions may be due to the supply of energy during litter decomposition, which can stimulate significantly microbial activity (Ma et al 2013). Alpine steppe soil was the Bsink^of CH 4 , and litter treatments either decreased or had no effect.…”
Section: Effects Of Litter Treatments On Soil C and N Dynamicsmentioning
confidence: 99%
“…Plant litter is the greatest source of soil organic matter (SOM), and its decomposition can form humus substances and organic layers in most natural ecosystems (Berg and Laskowski 2005). However, some studies claimed that litter inputs did not necessarily translate into increased SOM sequestration in nutrition-limited ecosystems, because microbial activity may be stimulated to such a degree that most or all of the added litter is decomposed rapidly (Rinnan et al 2008;Ma et al 2013). In our study, litter treatments (single and mixed litter) generally enhanced SOC, TN, WSOC, and WSON compared to the initial soil (Tables 3 and 4), and thus, it is reasonable to conclude that, in the cold and semiarid alpine steppe, litter decomposition is still able to cause SOM sequestration due to relatively low microbial activity (Table 4).…”
Section: Effects Of Litter Treatments On Soil C and N Dynamicsmentioning
confidence: 99%
“…It has been shown that land use changes lead to great variation in soil microbial community composition in diverse ecosystems (Drenovsky et al, 2010), though their impacts depend on many factors, including the original vegetation that is being replaced and associated land management practices such as tillage and fallow periods, as well as related water and nutrient applications such as irrigation and fertilization (Scanlon et al, 2007;Ma et al, 2013;Yang et al, 2013;Chen et al, 2014). In one study, Drenovsky et al (2010) reported that distinct microbial communities were associated with land use types and disturbance at the regional scale in California.…”
Section: Introductionmentioning
confidence: 99%